Effect of Wood Waste as A Partial Replacement of Cement, Fine and Coarse Aggregate on Physical and Mechanical Properties of Concrete Blocks Units - Abed, Jasim Mohammed; Khaleel, Ban Ahmed (International Journal of Integrated Engineering, 2019)
Wood waste has been used in concrete in 19th century. Its light-weight and cost effectiveness are main recognized characteristics. To reduce the environmental burden, nowadays developed countries have opportunities to use wood waste in concrete construction. This research presents experimental program results on mechanical and physical properties of ninety-six specimens of concrete blocks units. The experimental program concluded three groups of mixes plus the control mix. In Group 1 and Group 2, sawdust waste has been used as a partial replacement of 10%, 15%, 20%, 25% and 30% by volume of cement and sand respectively. In Group 3, wood waste aggregate has been used as a partial replacement of 10%, 15%, 20%, 25% and 30% by volume of coarse aggregate. The specimens were conditioned for 28-days at 80±5% Relative humidity and 24±2°C and tested. Slump, compressive strength, water absorption, dry density, porosity and thermal conductivity tests have been conducted. The compressive strength of concrete blocks units decreased due to the effect of sawdust waste and wood waste aggregate by increasing the replacement ratio instead of cement, sand and coarse aggregate. The results showed the mixes of group1 and group2 produced structural concrete blocks units at 20% replacement ratio of sawdust waste instead of cement and sand respectively. Also, the results showed that light-weight concrete blocks units can be obtained at a 25% and 30% replacement ratio in all groups with satisfactory compressive strength. The optimum replacement ratio was about 20% in the three groups so that physical and mechanical properties were satisfactory. This may be considered a solution not only to the problem of the environment but also to the problem of economics in the design of buildings.